Literatur Review Sistematik: Plan of Action (POA) dalam Konteks Kesehatan - Winda Maser, Putri Cus; Rahmatunnisa, Virda; Hartono, Budi (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2025)
Background: Plan of Action (POA) is a strategic planning approach in healthcare systems to enhance service effectiveness. Poorly designed POA can lead to inefficiency, delayed disease detection, and reduced program effectiveness. Objective: To review the implementation of POA in case manager documentation, tuberculosis (TB) case detection, and hospital health promotion, as well as to identify solutions to its implementation challenges. Method: A literature review of three journals discussing POA in healthcare, analyzing strategies, challenges, and solutions. Results: POA improves case manager documentation, TB detection coverage, and patient health awareness. However, challenges remain, such as limited resources, community resistance, lack of supporting policies, and insufficiently trained healthcare workers. Conclusion: POA is effective in enhancing healthcare services when supported by strong policies, adequate resources, and active engagement from healthcare workers and the community.